A COMPARATIVE ANALYSIS OF FRENCH AND ZIONIST SETTLER COLONIALISM IN ALGERIA AND PALESTINE (Journal of Oriental Studies, 2024)
The paper explores and analyzes similarities and differences between French settler colonialism in Algeria and Jewish Zionist settler colonialism in Palestine. This study focuses on the history and historical development of French settler colonialism and Jewish Zionist settler colonialism by deploying the analytical framework of settler colonialism, and the comparative history of settler colonialism. Settler colonial studies and comparative settler colonialism allow for gaining insight into the genesis, and development of settler colonies. The intention behind the application of comparative settler colonialism, specifically in juxtaposing French settler colonialism in Algeria and Jewish Zionist settler colonialism in Palestine is to identify overlaps, similarities as well as differences between these settler polities. The results of this study have shown that French and Zionist settler colonialism share numerous similarities and features. The most important feature that these settler colonialisms adhere to is the logic of elimination, which is defined as policies and practices of settler colonial policies aimed at the dispossession, displacement, ethnic cleansing, genocide, as well as cultural assimilation of the indigenous populations. In this case, both French and Zionist settler colonialisms have subscribed and followed the logic of the elimination of the natives. Yet as opposed to French settler colonialism, Zionist settler colonialism has been less interested in cultural assimilation and integration of the indigenous people of Palestine into settler society. Another conspicuous difference between French and Zionist settler colonialism is that while French settler colonialism is already defunct, Zionist settler colonialism has managed to survive and persist. The current study contributes to settler colonial studies and the comparative history of settler colonialism. Moreover, our research can inform other studies in the field of settler colonialism, and we suggest that more research into comparative settler colonialism needs to be undertaken.Keywords: France, Zionism, Algeria, Palestine, colonialism, settler colonialism